Identification of Genius Loci in Historical District with The Case Study of Two Alleys in Purbayan, Kotagede, Yogyakarta - Anindyta, Maheswari Rahajeng; Putri, Aulia Herlina; Agustiananda, Putu Ayu P.; Rafi , Fitri Amalia (Sinektika: Jurnal Arsitektur, 2026)
Exploring the concept of "genius loci," which refers to the spirit or essence of a place shaped by human interactions and the surrounding environment, this study focuses on the historical district of Kotagede in Yogyakarta, Indonesia. It examines how the unique architectural and cultural characteristics of two alleys, Gang Rukunan RW 07 Purbayan and Gang Rukunan RW 09 Purbayan, contribute to their distinct identities. Gang Rukunan RW 09, also known as Between Two Gates, is particularly renowned for its well-preserved traditional Javanese architecture and communal spaces. Using a phenomenological qualitative research method, including observations and interviews, the research identifies three key aspects of genius loci: image, space, and character. The findings reveal that while Gang Rukunan RW 09 is celebrated for its traditional architecture, Gang Rukunan RW 07, despite undergoing modern transformations, retains significant elements of its cultural identity through active social interactions among residents. The study highlights the challenges posed by modernization, which often threatens the preservation of traditional values and architectural integrity. Ultimately, the paper underscores the importance of understanding and maintaining the genius loci of historical areas to foster community identity and cultural heritage amid the pressures of urban development.